Geomorphology of the La Yesera proluvial fan that is partly occupied by the town of San José Los Molinos, Ica-Peru - Meléndez de la Cruz, Juan Felipe (2020)
Geomorphologically, the La Yesera torrent is a unit of the relief that is characterized by the occurrence of deep mass movements because intense weathering and erosion processes occur in its reception basin. Geologically, the reception basin of the said unit is a batolith with rocks deformed by fractures and failures. The drainage channel and fan of the torrent is covered with powerful layers of mud (sand) and blocks (clasts and bowling). The proluvial fan of the torrent is very dissected due to the impact and the sharp action of alluvium (huaycos) during the recent quaternary (last 10,000 years). The aforementioned proluvial fan is located adjacent to the Ica River, on its left bank. The paved road that connects the town of San José Los Molinos with the city of Ica cuts the aforementioned range into two sectors. The first is adjacent to the Ica River that is occupied by farmland and some homes. In the second sector is located the town of San José Los Molinos that is exposed to the impact of floods being a disaster risk space.